Les collections de l’École de dessin de Montpellier (1779-1825) - Pierre Stépanoff (In Situ)
If the Musée Fabre has been created in 1825 by the painter François-Xavier Fabre, the Fabre museum of Montpellier has an older origin. In the year 1779, a free drawing school was founded in the southern french city. Over the years and after its multiple metamorphoses, until the museum’s creation in 1795, a large collection of models was assembled and made available to students. Unfortunately, this pedagogical equipment has gradually disappeared to give way to a more strictly patrimonial and artistic conception of the collections. Recent research and the organization of an exhibition on this subject at the musée Fabre in 2017-2018 now allow us to perceive this history, as well as to understand the genesis of the museum of Montpellier, at the end of the Ancien Regime and during the French Revolution. It underlines the ambiguity of the definition of this first museum, between instruction and pleasure.